2007
DOI: 10.1111/j.1365-2311.2007.00887.x
|View full text |Cite
|
Sign up to set email alerts
|

Male behaviour over the season in a wild population of the field cricket Gryllus campestris L.

Abstract: 1. Cricket model systems have greatly enhanced our knowledge about mate choice and sexual selection. However, no studies exist that take seasonal dynamics into account and that follow individual males over the complete adult stage in the wild. In the present study, all adult field crickets (Gryllus campestris L.) were individually marked and measured in a population in central Germany and their behaviour was followed over their life from May to July 2000.2. The population reached a maximum of 108 males within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Simmons (1992Simmons ( , 1995 showed in cross-sectional studies that mated males of G. campestris were older, larger and more symmetrical than unmated males. In an accompanying paper we have shown that large males eclose to adults earlier and therefore, age and body size are correlated in the beginning of the season (Ritz and Köhler 2007).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Simmons (1992Simmons ( , 1995 showed in cross-sectional studies that mated males of G. campestris were older, larger and more symmetrical than unmated males. In an accompanying paper we have shown that large males eclose to adults earlier and therefore, age and body size are correlated in the beginning of the season (Ritz and Köhler 2007).…”
Section: Introductionmentioning
confidence: 84%
“…The two fitness variables lifespan and number of mates were transformed into relative fitness measures by dividing them by their population mean. Pronotum width and body mass of male crickets were highly correlated (r = 0.81, Ritz and Köhler 2007) and therefore, body condition (residual body mass) was used instead of body mass. Body condition was calculated by regressing body mass over pronotum width and saving residual body mass as ratio of the predicted mass.…”
Section: Selection Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether such displays serve to reinforce winner dominance (browbeating) or to communicate victory to mates or rivals (advertising; [5,19]) is unknown. Given that cricket densities can be high [12,20], and mate attraction and contests occur in close proximity [21], contests are likely to occur with female and male audiences nearby. We therefore investigated whether winners' behaviour during and after contests is influenced by the presence and sex of an audience.…”
Section: Introductionmentioning
confidence: 99%
“…In this case the 510 daily rate was calculated over the first 24 h using distances observed for all the 511 individuals in the released population, recording mean rates of 1.7-3.8 m day -1 for 512 juveniles and 3.0-6.3 m day -1 for adults (Diekötter et al, 2005). For field crickets 513 (Gryllus campestris L.) living in herb-rich meadows, rates were obtained for all males, 514 which moved a mean distance of 2.8 m day -1 (Ritz & Kohler, 2007). Considered 515 together these results suggest that, compared to other cricket species for which data 516 are available, dispersal within wood cricket populations is limited, and the species can 517 be considered as relatively sedentary.…”
mentioning
confidence: 99%